Simulation-Based Assessment of Anesthesiology Residents' Competence: Development and Implementation of the Canadian National Anesthesiology Simulation Curriculum (CanNASC). Issue 2 (April 2017) - Chiu, M.; Tarshis, J.; Antoniou, A.; Bosma, T. L.; Burjorjee, J. E.; Cowie, N.; Crooks, S.; Doyle, K.; Dubois, D.; Everett, T.; Fisher, R.; Hayter, M.; et al.
Abstract : (Abstracted from Can J Anaesth, 63(12):1357–1363, 2016) The specialty of anesthesiology will adopt Competence By Design in residency developed by the Royal College of Physicians and Surgeons of Canada (RCPSC). Frequent and contextualized assessment of trainees is the foundational concept of competency-based medical education.